The Current State and Prospects of Chinese Teaching in the United States. Issue 6 (1st November 2016) - Luo, Ling
Abstract: Chinese teaching arose in the United States in the 1870s, which was relatively early compared to other regions, but due to issues of politics and funding it was perennially marginalized. Chinese teaching in the United States did not see development until the early 1960s, when it began receiving funding from the U.S. government. Owing to the global political landscape and China's growing strength, Chinese teaching in the United States has been reshaped: the learning age has grown younger, the learning regions have expanded, and the learning content and teachers have diversified. Chinese teaching in the United States is not a simple matter of education: rather, it is closely bound up with the blending of political and economic development, culture, and ideology. From an educational perspective, China's Confucius Institute Headquarters and experienced teachers in the United States should work in concert to formulate teaching materials and train qualified teachers to resolve issues related to the sustainable development of Chinese teaching in the United States.